2015
DOI: 10.1111/exd.12741
|View full text |Cite
|
Sign up to set email alerts
|

NKp46 regulates the production of serine proteases and IL‐22 in human mast cells in urticaria pigmentosa

Abstract: NKp46 (natural cytotoxic receptor 1/CD335) is expressed on natural killer cells and Th2-type innate lymphocytes. However, NKp46 expression in human mast cells has not yet been reported. Here, we explored the expression of, and possible role played by, NKp46 in such cells. NKp46 protein was expressed in human mast cells in urticaria pigmentosa principally of the tryptase-positive/chymase-negative type (MCT), but not in human non-neoplastic skin mast cells of the tryptase-positive/chymase-positive (MCTC) type. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Studies using mast cell-deficient mice, such as Kit W/Wv mice and Kit Wsh/Wsh mice, revealed that mast cells protect against parasitic infections including Strongyloides ratti and Strongyloides brasiliensis [7,8], as well as the venoms of honeybees or vipers [9]. Mast cells are (KIR) 2DL4 [19][20][21][22][23][24][25][26][27][28][29][30][31]. These include inhibitory receptors characterized by immunoreceptor tyrosine-based inhibitory motifs (ITIMs) within their cytosolic domains ( Figure 1) [32].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using mast cell-deficient mice, such as Kit W/Wv mice and Kit Wsh/Wsh mice, revealed that mast cells protect against parasitic infections including Strongyloides ratti and Strongyloides brasiliensis [7,8], as well as the venoms of honeybees or vipers [9]. Mast cells are (KIR) 2DL4 [19][20][21][22][23][24][25][26][27][28][29][30][31]. These include inhibitory receptors characterized by immunoreceptor tyrosine-based inhibitory motifs (ITIMs) within their cytosolic domains ( Figure 1) [32].…”
Section: Introductionmentioning
confidence: 99%
“…KIT-mediated and IgE receptor-mediated responses in mast cells can be modified by other receptors expressed on the cell surface. These include inhibitory receptors [7][8][9][10][11][12][13][14][15][16][17] characterized by immunoreceptor tyrosine-based inhibitory motifs (ITIMs) within their cytosolic domains [18]. ITIMs comprise the homology sequence In previous work, we identified the expression in human mast cells of the inhibitor receptor killer inhibitory receptor (KIR) 2DL4 (CD158d) [16,17].…”
Section: Inhibitory Receptorsmentioning
confidence: 99%
“…Therefore, inhibition of KIT signalling would be useful when treating this neoplastic disorder . A promising means to this end is stimulation or blocking of receptors expressed by human mastocytosis cells . Another SLAM family member CD84 would be also a promising target to inhibit KIT signalling.…”
Section: Introductionmentioning
confidence: 99%